The summarized of EASL 2017 Clinical Practice Guidelines on the management of hepatitis B virus infection - Idilman, Ramazan (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Idilman R. The summarized of EASL 2017 clinical practice guidelines on the management of hepatitis B virus infection. Turk J Gastroenterol 2017; 28: 412-6.